Atypical myopathy in the South‐East of England: Clinicopathological data and outcome in hospitalised horses. (28th January 2018) - Dunkel, B.; Ryan, A.; Haggett, E.; Knowles, E. J.
Summary: This retrospective case series describes clinicopathological data and outcome of hospitalised atypical myopathy (AM) cases in the South‐East of England. The study aimed to describe the frequency of metabolic abnormalities (hyperglycaemia, hyperlactataemia, hypertriglyceridaemia) and outcome in AM cases in the South‐East of England and test the hypothesis that serum creatine kinase (CK) activity and blood glucose, lactate and triglyceride concentrations are associated with outcome. Medical records (2011–2017) from three referral hospitals were reviewed for cases with a clinical diagnosis of AM. A previously described algorithm was applied and cases were included if a diagnosis of AM was considered highly likely. In cases admitted after 2013 known or possible exposure to sycamore trees was also required for inclusion. Sixty‐four animals were included, 44% (28/64) survived. Hyperglycaemia, hyperlactataemia and hypertriglyceridaemia were present in 76%, 89% and 92% of horses on admission, respectively. Survivors had lower blood lactate concentrations (survivors: median 3.5 mmol/L; range 0.5–10.4 mmol/L vs. nonsurvivors: median 7.3 mmol/L; range 2.5–16.5 mmol/L; P = 0.011) and serum CK activities (survivors: median 38, 369 U/L; range 7024–570, 498 U/L vs. nonsurvivors: median 172, 687 U/L; range 2036–570, 953 U/L; P = 0.027) on admission when compared to nonsurvivors. Increasing CK activity (P = 0.008) and triglyceride concentrations (P = 0.038) during hospitalisation were associated with nonsurvival. More nonsurvivors required sedation (18/29; 62.1% vs. 4/22; 18.2%; P = 0.002). The prognosis for hospitalised horses with AM is guarded and outcome in this population was associated with admission CK activity and lactate concentrations, and increasing CK activity and triglyceride concentrations and need for sedation during hospitalisation.